EFFECT OF INVESTMENT DECISION AND DIVIDEND POLICY ON FINANCIAL PERFORMANCE - Eltie Christi Sandag; Erawati Kartika; Kunto Atmojo; Ingra Sovita; Musran Munizu (Journal of Innovation Research and Knowledge, 2023)
This study aims to determine and analyze effect of investment decision and dividend policy on financial performance. This research uses causal quantitative research. Population used in this study are Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. This study used a purposive sampling method for sampling. Based on predetermined criteria, the number of samples collected is 15 companies. Statistical analysis in this study used multiple linear regression analysis through partial (t) test. The results show that investment decision has a significant effect on financial performance at Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2018 to 2022. Dividend policy has a significant effect on financial performance at Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2018 to 2022.